Hydrophilic Versus Hydrophobic Acrylic Intraocular Lens Implantation in Paediatric Cataract Surgery - Thapa, Bikram Bahadur; Gurung, Nanda Kumari (Journal of Nepalgunj Medical College, 2023)
Introduction: The selection of intraocular lens is still debatable in paediatric eye. Due to low cost and fewer intra-operative complication hydrophilic acrylic intraocular lens are implanted in volume in low income countries. There is lack of comparative study of this type of lens with hydrophobic lens in paediatric population. Aims: To compare the outcomes of hydrophilic acrylic lens and hydrophobic acrylic lens in paediatric cataract surgery. Methods: Out of 48 eyes included in the study, the Group A (n =24) eyes were implanted with acrylic hydrophilic intraocular lens, and the Group B (n =24) were implanted with acrylic hydrophobic intraocular lens. The children were evaluated pre, intra and postoperatively for different parameter. Results: The mean age was 6.6±2.7 years at the time of surgery. The most common type of cataract was zonular (58% in Group A and 50% in Group B). Postoperatively, corneal edema was seen in 7(29%) eyes in group A and in 2(8%) eyes in group B. The mean follow-up was 16.9±2.9 months. At one year, the position of the intraocular lens was in the capsular bag in 20 eyes (88.33%) and 24 eyes (100 %) in the group A and B, respectively. Clear visual axis was present in 22 eyes in Group A and 24 eyes in Group B. Posterior capsule opacification occurred in 12(50%) eyes in Group A and 6(25%) eyes in Group B. Two (8.3%) eyes in group A underwent surgical membranectomy due to visual axis opacification. The mean LogMAR visual acuity was 0.56 and 0.52 in group A and B respectively at one year. Conclusion: Hydrophilic acrylic intraocular lens are good alternative to hydrophobic intraocular lens in Nepal in the treatment of paediatric cataract.